CONJUGATED LINOLEIC ACID IN MILK AND FERMENTED MILKS: VARIATION AND EFFECTS OF THE TECHNOLOGICAL PROCESSES - Luis Felipe Gutiérrez Alvarez (Universidad de Antioquia, 2016)
Background: Conjugated linoleic acid (CLA) is a generic term used to describe a group of geometric and positional isomers of linoleic acid with a conjugated double bond system. CLA-isomers have been widely studied because of their important biological activity and their protective effects against several diseases, such as obesity, atherosclerosis, chronic inflammatory diseases, and cancer. Consequently, these biomolecules have attracted much attention from the dairy industry, since they are naturally found in ruminants’ milk, and because the development of CLA-enriched dairy foods can be a good economic opportunity given the growth of the functional foods market, in which the dairy industry plays an important role. Objectives: This work presents a comprehensive review of the following aspects: (i) The synthesis and concentration of the CLA-isomers in milk, and the main strategies employed to increase their content in a natural manner; (ii) The influence of the main technological treatments applied to milk on the concentration of CLA-isomers; and (iii) The effects of milk fermentation on the content of CLA-isomers, and the challenges of this technological process, which has been though as a promissory alternative to naturally increase the content of CLA in fermented dairy products. Methods: Information available in various databases was reviewed. A total of 103 articles were selected on the basis of their relevance and scientific-technical quality. Results: The CLA concentration in cows’ milk normally ranges between 2 and 37 mg/g fat, and is mainly affected by the dietary regime offered to the animals. From the total CLA-isomers, rumenic acid represents between 75 and 90%. The technological processes normally applied to milk (thermal processing, high pressure processing, and fermentation) might cause slight changes on the CLA concentration, but the mechanisms causing these changes have not been still established. The increase in CLA concentration by milk fermentation is strain-dependent, because of the different linoleate isomerase activity of the species. . Conclusions: Although several studies have reported increases in the concentration of CLA in milk and fermented milks in a natural manner, they are fairly moderate, and the obtained levels of CLA are significantly lower than those recommended to achieve therapeutic effects.